Case Report: Severe COVID-19 Pneumonia in a Patient With Relapsed/Refractory Hodgkin’s Lymphoma - Yonal-Hindilerden, Ipek; Hindilerden, Fehmi; Mastanzade, Metban; Tiryaki, Tarik Onur; Tasan-Yenigun, Sevim; Bilen, Yusuf; Aksoz, Selcuk; Cagatay, Arif Atahan; Nalcaci, Meliha (Frontiers in Oncology, 2021)
First identified in China in December 2019, coronavirus disease 2019 (COVID-19) has rapidly evolved into a global pandemic. The presence of haematological malignancies are expected to increase the risk of adverse outcomes from this viral infection due to the immunosuppression brought about by the underlying cancer and the effects of therapy. We present a 55-year-old woman diagnosed with relapsed/refractory Hodgkin’s lymphoma (HL) who had been heavily pretreated with multiagent chemotherapy, autologous hematopoietic stem cell transplantation (autoHCT), allogeneic hematopoietic stem cell transplantation (alloHCT) and was complicated with EBV associated posttransplant lymphoproliferative disease (PTLD) and chronic graft-versus-host-disease (GVHD). The patient was recently treated with brentuximab and donor lymphocyte infusion (DLI) for relapse after alloHCT. She suffered from severe COVID-19 pneumonia and eventually succumbed to acute respiratory distress syndrome (ARDS) and multiorgan failure. Of note, this is the first reported case of COVID-19 in a HL patient who was being treated with brentuximab for relapse after alloHCT.